2017
DOI: 10.1097/dcr.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anal Acoustic Reflectometry in the Evaluation of Men With Passive Fecal Leakage

Abstract: Anal acoustic reflectometry is a sensitive test of anal sphincter function and, unlike anal manometry, can discriminate male leakers from continent subjects. An identifiable abnormality has been detected using anal acoustic reflectometry, which may further our understanding of the pathogenesis in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Few reports to date, however, have assessed the functional cooperation between the IAS and EAS, as the two sphincters were usually examined separately. Another reason of few interests in the distal IAS-EAS complex was found in a fact that, with an aid of the levator ani muscle, a closing pressure is highest in the proximal anal canal, not in the distal [5,10,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports to date, however, have assessed the functional cooperation between the IAS and EAS, as the two sphincters were usually examined separately. Another reason of few interests in the distal IAS-EAS complex was found in a fact that, with an aid of the levator ani muscle, a closing pressure is highest in the proximal anal canal, not in the distal [5,10,33].…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, another term "longitudinal anal muscle" has been used in the pelvic floor anatomy [16,21,28,30]. Despite recent advances in imaging technology [5,10,22,33], few studies have evaluated site-dependent differences in the topographical relationship between the internal and external anal sphincters (IAS, EAS). Endoanal ultrasound evaluation of 12 men and 14 women showed that: (1) the anterior IAS is shorter than the posterior and lateral IAS; and (2) the distance from the lateral EAS to the pubis is significantly longer than the distance from the posterior EAS to the pubis [29].…”
Section: Introductionmentioning
confidence: 99%
“… Investigate newer technologies for measuring anal sphincter functions . By distending the anal sphincter, anal acoustic reflectometry and the anal barostat can assess the integrity and distensibility of the anal sphincter barrier 93–97 . A fecobionic silicon bag that resembles the consistency of normal stool has pressure and motion sensors that record pressures, anorectal angles, and expulsion velocity during defecation 98,99 …”
Section: Methodsmentioning
confidence: 99%
“…of the anal sphincter barrier. [93][94][95][96][97] A fecobionic silicon bag that resembles the consistency of normal stool has pressure and motion sensors that record pressures, anorectal angles, and expulsion velocity during defecation. 98,99 The incremental utility of these devices for understanding the pathogenesis or guiding the management of FI or DD remains to be established.…”
Section: Pressure Measurement In the Posterior Distal Pressure Zonementioning
confidence: 99%